2012
DOI: 10.1007/s00330-012-2431-4
|View full text |Cite
|
Sign up to set email alerts
|

Significance of pulmonary nodules in patients with colorectal cancer

Abstract: • Pulmonary nodules in colorectal cancer patients raise concern about metastasis. • Baseline and follow-up chest X-ray in colorectal cancer can be abandoned. • CT is the best technique for assessing PNs in colorectal cancer. • Short-interval CT follow-up advisable for PNs larger than 5 mm with irregular margins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 35 publications
1
6
1
Order By: Relevance
“…The careful evaluation of morphologic features is an essential step in pulmonary nodules assessment (13). Although several studies (2224) have sought to identify significant image features for metastatic nodules, there is no consensus regarding the definition of IPNs, which led to slight differences between our results and previously published ones. In our study, we found that significant morphological features associated with pulmonary metastasis were long-axis diameter, density, and contour.…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…The careful evaluation of morphologic features is an essential step in pulmonary nodules assessment (13). Although several studies (2224) have sought to identify significant image features for metastatic nodules, there is no consensus regarding the definition of IPNs, which led to slight differences between our results and previously published ones. In our study, we found that significant morphological features associated with pulmonary metastasis were long-axis diameter, density, and contour.…”
Section: Discussioncontrasting
confidence: 90%
“…As reported by many other studies, nodule diameter is a reliable indicator of malignant potential (22, 23, 25). We found that solid nodules are more likely to be metastatic lesions.…”
Section: Discussionsupporting
confidence: 66%
“…Accordingly, we suggest that regular chest CT scans should be considered to diagnose pulmonary metastasis early. 13 Several widely recognized staging systems are available for evaluating HCC, such as the Barcelona Clinic Liver Cancer (BCLC) classification, TNM staging systems and American Joint Committee (AJCC) cancer staging system. 14 Many variables were identified as prognostic factors and were included in cancer staging systems, including the tumor size, vascular invasion, performance status, distant metastases, and liver function indicators such as serum albumin and bilirubin levels.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the follow-up of these patients should be more intensive. Thus, regular chest CT scans instead of chest X-ray should be taken (Pomerri et al , 2012) in order to diagnose PM early. The nomogram may also be a useful tool in deciding organ allocation for secondary liver transplantation for HCC patients who have been initially treated with partial hepatectomy.…”
Section: Discussionmentioning
confidence: 99%